Rakergab Makehjapol I : thema, Tegaknya hukum dan keadilan merupakan unsur mutlak bagi keberhasilan Pelita IV (Direktorat Jenderal Pembinaan Badan Peradilan Umum, 1984)
Proceedings of joint working conference of the Supreme Court, Dept. of Justice, Attorney General and Indonesian Police Force in connection with application of Indonesian new criminal code.